(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
This paper explores the scientific view that has been gathered on the contributions and advantages of sports activities and yoga exercises in schools for each adolescent, specially school going children. Any form of physical activity good for children of any age either it is any form of Sports activities, yoga exercises, Zumba, aerobics etc any form of physical activities helps in strengthen the body and improve bone density. There are so many reasons to do sports activities. Daily based physical activities in early age make child sound and healthy with strong bones and good body coordination. Sports activities were the part of our culture from last many decades in old ages sadhu mahatmas use yoga to maintain their body system and Raja Maharaja were also used to play different games and sports to maintain their life healthy and strong. Sports activities provide over all benefits to every individual. Research shows that sports activities provide holistic development to school going children and Number of research proves children’s development in a number of domains: